Fibroblasts support migration of monocyte‐derived dendritic cells by secretion of PGE2 and MMP‐1. Issue 8 (22nd May 2015) - Saalbach, Anja; Janik, Tobias; Busch, Matthias; Herbert, Diana; Anderegg, Ulf; Simon, Jan C.
Abstract The outcome of a cutaneous immune response is critically dependent upon the ability of dendritic cells (DC) to migrate from skin to the draining lymph nodes – a process that is influenced by the cutaneous tissue microenvironment. Here, the role of fibroblasts – a major component of the dermal microenvironment – on the migratory capacity of monocyte‐derived DC (MoDC) was investigated in a 3D collagen I matrix. Indeed, dermal fibroblasts supported the migration of pre‐activated MoDC through a 3D collagen I matrix. Activation of human MoDC resulted in the release of TNFα and IL‐1β that in turn stimulated MMP‐1 (human collagenase) and PGE2 secretion by human dermal fibroblasts. Transmigration assays confirmed the importance of fibroblast‐derived MMP‐1 and PGE2 for the migration of MoDC through a 3D collagen I matrix. Finally, in mice initiation of inflammation by induction of an irritant contact dermatitis or a psoriasis‐like skin inflammation, the expression of the PGE2 generating cox‐2 and the mouse collagen I degrading enzyme matrix metalloproteinases (MMP)‐13 was strongly up‐regulated. Our study indicates that MoDC are able to instruct dermal fibroblasts resulting in enhanced migratory capability of MoDC, thus highlighting the role of a crosstalk of DC with their stromal microenvironment for the control of cutaneous immune responses.